Thermal Conductivity Measurement of Insulating Materials under non-Stationary Heat Flow (2019)
A device to measure thermal conductivity in thermal insulating solid materials commonly used in buildings was developed following a one-dimensional model of heat flow through a plate of the material to be evaluated. The temperature gradient between the plate faces was measured as a function of time by means of a set of type T thermocouples. A circuit with commercial microcontrollers was designed to control the instrument’s mechanisms, the acquisition and the treatment of data. In preliminary tests with some materials, thermal conductivity values similar to those reported in the literature were obtained by using a linear adjustment with R values between 0.90 and 0.98. This device turns out to be a good instrument for measuring thermal conductivity because it has several advantages, such as: easy implementation, sample size, measurement method; compared to those using traditional methods.